Interações no Setor Escuro do Universo - Castro, Roly David Rodriguez (2012)
Interactions between dark matter and dark energy modify the dynamics of the cosmological standard model. In particular, they may be relevant in attempts to alleviate the cosmic coincidence problem. In this dissertation we study a class of interactions that result in a power law with respect to the scale factor for the ratio of the energy densities of both dark components. We generalize this approach to include time-varying equations of state for the dark energy. We obtain analytic solutions for two special cases. We confront the theoretical results with observations from supernovas type Ia and other observational data. We perform a statistical analysis and classify models with and without interactions according to information criteria. The relevance of the interacting models for the coincidence problem is discussed.